Grammatical Errors and the Impacts in Australasian Parliamentary Debate - Elok Widiyati; Dinta Amelia (Journal of Advanced Multidisciplinary Research, 2026)
Debate is a productive speaking skill where students from pro and cons sides argue their constructive arguments to win. It deals with students’ grammar accuracy in showing the exact motion nuance and consistent context delivered. However, there were very limited research conducted in the area of debate inaccuracy dealing with grammar from Australasian Parliamentary debate system. Through the debate class conducted by the students, gaps in the previous studies in grammatical error addressed. Therefore, this article aims to find out the students’ grammatical errors types in the debate class and highlights factors, impacts, and strategies to avoid the errors. The researchers used descriptive quantitative research design with an open questionnaire and transcribed video. The respondents were the students of third semester majoring English Education. The researchers gathered the data from offline debate class. The data was analyzed based on the morphological errors. The findings showed that the most frequently error produced was misselection 63.34%, omission 32%, overinclusion 2%, misordering 1.33%, and blend 1.33%. Surprisingly, a new sub type of omission found as adjective. It can be concluded that the grammatical errors in debate dealt with all the types but it did not happen to the all sub types. The regular grammatical errors made by the students had the higher the impacts to the internal aspect compared to the external aspect referring to the technicalities and adjudication. To conclude, it is very important to analyze the students’ grammatical errors in their debate performance to boost their clear argument and rebuttal delivery to minimize ambiguity. Therefore, it would be easily understood by the opponents and adjudicators.